2020
DOI: 10.3390/min10121092
|View full text |Cite
|
Sign up to set email alerts
|

Sulfates from the Pyrite Ore Deposits of the Apuan Alps (Tuscany, Italy): A Review

Abstract: The occurrence of sulfate minerals associated with the pyrite ores of the southern Apuan Alps has been known since the 19th century but modern mineralogical studies started only in the last decade. Sulfate assemblages were identified in all the pyrite ore deposits from the studied area but the more impressive associations were discovered in the Fornovolasco and Monte Arsiccio mines. Their study allowed to improve the knowledge of the sulfate crystal-chemistry and to achieve a better understanding of the acid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Natural epsomite is a common hydrous magnesium sulfate with the general formula Mg(SO 4 )·7H 2 O (Anthony et al, 1990; Giordani, Meli, et al, 2022). Natural epsomite occurs mainly on the walls of mines, caves, and outcrops of sulfide‐bearing magnesian rocks (e.g., dolostone) but also as a product of evaporation at mineral springs and saline lakes, and rarely as fumarolic sublimate (Anthony et al, 1990; Biagioni et al, 2020). Epsom salt is widely used in many fields, and it has numerous medical and pharmaceutical applications, such as the treatment of cardiac arrhythmia, acute asthma, eclampsia, and gallstones (Ruiz‐Agudo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Natural epsomite is a common hydrous magnesium sulfate with the general formula Mg(SO 4 )·7H 2 O (Anthony et al, 1990; Giordani, Meli, et al, 2022). Natural epsomite occurs mainly on the walls of mines, caves, and outcrops of sulfide‐bearing magnesian rocks (e.g., dolostone) but also as a product of evaporation at mineral springs and saline lakes, and rarely as fumarolic sublimate (Anthony et al, 1990; Biagioni et al, 2020). Epsom salt is widely used in many fields, and it has numerous medical and pharmaceutical applications, such as the treatment of cardiac arrhythmia, acute asthma, eclampsia, and gallstones (Ruiz‐Agudo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Alunogen is a hydrated aluminium sulphate with the formula Al 2 (SO 4 ) 3 •17H 2 O, regarded as a grandfather mineral species because it has been known since 1832 [1]. Alunogen is a rather widely distributed mineral reported as an acid mine drainage mineral and lowtemperature fumarolic mineral or pseudofumarolic at coal fires [2][3][4][5][6]. The early study of its optical properties has shown that they considerably vary depending on the H 2 O content in the mineral [7].…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional arrangement of such chains produces the framework, with two types of cavities occupied by A-site cations and Al(H 2 O) 6 octahedra [12,15] (Figure 1). Most of the voltaite-group minerals are cubic, Fd-3c, with the exception of pertlikite which is tetragonal, I4 1 /acd, as the result of symmetry lowering due to Fe-Mg ordering in one crystallographic site [3,4,12,[16][17][18]. For synthetic samples [12], cubic and tetragonal modifications were observed forming even sectorial metry lowering due to Fe-Mg ordering in one crystallographic site [3,4,12,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the voltaite-group minerals are cubic, Fd-3c, with the exception of pertlikite which is tetragonal, I4 1 /acd, as the result of symmetry lowering due to Fe-Mg ordering in one crystallographic site [3,4,12,[16][17][18]. For synthetic samples [12], cubic and tetragonal modifications were observed forming even sectorial metry lowering due to Fe-Mg ordering in one crystallographic site [3,4,12,[16][17][18]. For synthetic samples [12], cubic and tetragonal modifications were observed forming even sectorial crystals.…”
Section: Introductionmentioning
confidence: 99%